APPLICATIONS OF COMPUTATIONAL FLUID DYNAMICS IN MECHANICAL ENGINEERING (SERIES 6) (2026)
This sixth series, Computational Fluid Dynamics Applications in Mechanical Engineering, places a special emphasis on biomedical engineering applications. It provides an in-depth exploration of the fundamental principles and practical implementations of CFD within the biomedical domain. Furthermore, this book highlights how computational modeling serves as a vital tool for understanding fluid behavior in physiological systems and for advancing the design and optimization of biomedical devices. Covering topics such as blood flow simulation, respiratory airflow analysis, and fluid–structure interaction in prosthetics and implants, the book integrates theoretical foundations with case-based applications. Emphasis is placed on the interdisciplinary nature of CFD, bridging engineering, biology, and medicine to foster innovation in healthcare technology. This volume serves as an essential reference for biomedical engineering students, researchers, and professionals seeking to apply computational techniques to enhance biomedical research, diagnostics, and device development.